The Presidio and Militia on the Northern Frontier of New Spain A Documentary History, Volume I, 1570-1700 - Naylor, Thomas H. (University of Arizona Press, 2021)
Reports, orders, journals, and letters of military officials trace frontier history through the Chicimeca War and Peace (1576-1606), early rebellions in the Sierra Madre (1601-1618), mid-century challenges and realignment (1640-1660), and northern rebellions and new presidios (1681-1695).